Cluster Policies, Organising Capacity and Regional Resilience: Evidence from German Case Studies - Kiese, Matthias; Hundt, Christian (Raumforschung und Raumordnung | Spatial Research and Planning, 2014)
Resilience refers to the ability of a regional economy to recover from external shocks and to return to a sustainable growth path afterwards. This paper departs from the assumption that by improving a region’s organising capacity, cluster policies can strengthen regional resilience. We argue that the impact of cluster policies on regional resilience depends on the portfolio of clusters targeted for promotion, which may increase specialisation, unrelated or related variety in a region’s economic fabric. Based on a multidimensional model of cluster policies, case study evidence from seven German regions is drawn from an interview survey of 145 practitioners, policy advisors and independent observers. By illustrating the connections between cluster policy, organising capacity, and specialisation versus variety, these findings can be linked conceptually to regional economic resilience. This argument allows for some policy recommendations and the formulation of issues for further research.
Keywords: Cluster policy; Organising capacity of regions; Specialisation; Related variety; Regional resilience; Germany